2006
DOI: 10.1086/498521
|View full text |Cite
|
Sign up to set email alerts
|

Single-Day, Patient-Initiated Famciclovir Therapy for Recurrent Genital Herpes: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Background. Orally administered antiviral therapy for genital herpes improves the time to lesion healing and resolves symptoms during an outbreak. Although traditional therapy for a recurrent episode for healthy adults has consisted of twice-daily dosing for 5 days, recent studies have indicated that shorter courses of antiviral therapy are effective. This study was conducted to assess the efficacy and safety of a patient-initiated, single-day regimen of famciclovir therapy, compared with placebo, in immunocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 23 publications
(28 reference statements)
9
55
0
2
Order By: Relevance
“…The results from the famciclovir arm of this study were very consistent with those of the famciclovir arm of Aoki's placebo-controlled study 10 .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The results from the famciclovir arm of this study were very consistent with those of the famciclovir arm of Aoki's placebo-controlled study 10 .…”
Section: Resultssupporting
confidence: 82%
“…The benefits of short-course episodic therapy include convenience, reduced cost and improved compliance. Several abbreviated short-course regimens have been shown to be as effective as traditional 5-day regimens for recurrent episodes, including 3-day therapy with valacyclovir (500mg twice-daily) 7 , 2-day therapy with higher dose acyclovir (800mg 3 times daily), 2-day therapy with famciclovir (500mg initial dose, followed by 250mg twice-daily) 9 , and higher dose single-day famciclovir therapy (1 g for two doses) 10 (Table 1). While a small, uncontrolled observational study of valacyclovir 2 g twice-daily for 1 day reported median lesion duration of 5 days, randomized controlled studies with this regimen have yet to be performed 11 .…”
Section: Introductionmentioning
confidence: 99%
“…If viral reactivation had not yet occurred on day 1 of the study, it is possible that a single dose of famciclovir might have been more efficacious, as was the case when used as a prophylactic drug in humans with genital herpesvirus infections (Aoki et al, 2006;Spruance et al, 2006). Doses in the current trial were selected for their potential economic and logistic advantages.…”
Section: Discussionmentioning
confidence: 99%
“…If administered to humans when symptoms commence, famciclovir can reduce the time to remission of clinical signs due to herpes simplex virus (HSV)-1 (Spruance et al, 2006) or HSV-2 (Aoki et al, 2006;Bodsworth et al, 2008). Two randomized, double-masked trials have investigated the effect of a single dose of famciclovir initiated by human patients at the onset of prodromal symptoms; both demonstrated efficacy for treatment of genital herpesvirus infections (Aoki et al, 2006;Spruance et al, 2006). Penciclovir has been used to treat disease due to HSV-1, HSV-2, varicella zoster virus and Epstein-Barr virus (Razonable, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation